2022
DOI: 10.1126/sciimmunol.abi6763
|View full text |Cite
|
Sign up to set email alerts
|

Protein kinase R is an innate immune sensor of proteotoxic stress via accumulation of cytoplasmic IL-24

Abstract: Proteasome dysfunction can lead to autoinflammatory disease associated with elevated type I interferon (IFN-αβ) and NF-κB signaling; however, the innate immune pathway driving this is currently unknown. Here, we identified protein kinase R (PKR) as an innate immune sensor for proteotoxic stress. PKR activation was observed in cellular models of decreased proteasome function and in multiple cell types from patients with proteasome-associated autoinflammatory disease (PRAAS). Furthermore, genetic deletion or sma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 85 publications
0
31
0
1
Order By: Relevance
“…Besides, EIF2AK2 selectively regulates the transcription of genes functioning in immune response in SLE (39). In proteasomeassociated autoinflammatory cell models, the activation of EIF2AK2 is discovered responding to the decreased proteasome function (40). Numerous studies have demonstrated the indispensable role of IFI27 (Interferon (IFN)-a-inducible protein 27) in SLE (41)(42)(43).…”
Section: Discussionmentioning
confidence: 99%
“…Besides, EIF2AK2 selectively regulates the transcription of genes functioning in immune response in SLE (39). In proteasomeassociated autoinflammatory cell models, the activation of EIF2AK2 is discovered responding to the decreased proteasome function (40). Numerous studies have demonstrated the indispensable role of IFI27 (Interferon (IFN)-a-inducible protein 27) in SLE (41)(42)(43).…”
Section: Discussionmentioning
confidence: 99%
“…Davidson et al. demonstrate that PKR drives induction of type I IFN response in proteasome associated autoinflammatory syndromes depending on its cytosolic interactor IL-24 accumulation ( 69 ). We suggest that PKR may drive induction of type I IFN signaling in IP impaired human microglia depending on IL-24 accumulation.…”
Section: Discussionmentioning
confidence: 99%
“…Our data further suggest that type I IFN under these conditions is not driven by host nucleic acids cells, since inhibition of the nucleic acid receptors TLR3 and STING by dsRNA/TLR3 antagonist and H-151, r e s p e c t i v e l y h a d n o d i s c e r n a b l e i m p a c t o n S T A T 1 phosphorylation and/or ISG expression profile (Figures 3B, S8, S9). Given the described ability of the UPR/ISR to induce sterile inflammation (82), we next asked whether it participated in the PR619-mediated type I IFN response in NCI-H929 cells. To address this point, we took advantage of commercially available inhibitors targeting the UPR/ISR at different levels including 4µ8C, C16, A92 and guanabenz which inhibit IRE1a, PKR, GCN2 and eIF2a dephosphorylation, respectively (84)(85)(86).…”
Section: Both Upr and Isr Are Constitutively Activated In Nci-h929 Mm...mentioning
confidence: 99%